THE KNOWLEDGE OF YOUNG DENTIST ABOUT PATIENT SAFETY SYSTEM AT ISLAMIC DENTAL AND ORAL EDUCATION HOSPITAL SULTAN AGUNG SEMARANG - Khusnul Khotimah, Ghea Tri; Arbianti, Kusuma; Agustin, Erna Dwi (Jurnal Medali, 2023)
Background: Patient safety was a management system created to prevent injuries brought on by performing or refraining from performing an action that should had been undertaken. Individual performance in developing a patient safety culture was strongly influenced by a person's level of knowledge. This research was conducted to determine the level of patient safety knowledge among young dentists at the Islamic Dental and Oral Education Hospital of Sultan Agung.Method: The design of this descriptive observational research method was Cross Sectional. The research was carried out at the Islamic Dental and Oral Education Hospital of Sultan Agung with the participation of 70 young dentists. The sampling method employed was Random Sampling. The data were examined with a univariate test.Result: The results indicated that 28.6% of young dentists at the Islamic Dental and Oral Education Hospital of Sultan Agung had a good level of knowledge, while 40% had a decent level of knowledge, and 31.4% had a bad level of knowledge.Conclusion: The conclusion of this research was that the majority of young dentists at the Islamic Dental and Oral Education Hospital of Sultan Agung (40%) had adequate levels of expertise.